Accessing the use of crumb rubber and kaolinite to the resistance of asphalt to deformation - Mustafa Anthony Pitia (Uganda Christian university, 2025)
Flexible pavement performance is often reduced by rutting, fatigue and lack of durability especially under heavy traffic. This study aimed to improve bitumen by modifying it with Crumb rubber (CR) and kaolinite clay to enhance resistance to fatigue cracking. Waste tires were used due to their high elasticity. CR was added to 60-70 pen grade bitumen in proportions of 5%, 10%, 15% and 20%. Tests showed that 5% CR gave the best balance of thermal, fatigue and moisture resistance. To improve storage stability, kaolinite was added in amounts of 1%, 1.5%, 2% and 2.5% with 2% showing the best results.
Undergraduate